Spatial identity in Slovenia - Kosi, Danilo (Journal for Geography, 2013)
Social geographers link together spatial identities with social organization in term of full filing of the some needs. They claim that every individuals is install in specific space binding with it on the base of actions enable him peaceful, safe and comfortable life. In such a way man is connected with the space of living and consequently also identified with it. We can divide the factors causing spatial consciousness on traditional and modern. The traditional are historical memory, culture, art and landscape. Modern factors are social institutions, administration divisions, medias, economical companies and mass sport. In paper we try to make clear basic terms regarding spatial identities, like: spatial identity, identity of the space, regional identity, identity of the region, identity region, spatial belonging ness, consciousness and identity. Spatial identity means that one is identifying one self with the space that could be bigger or smaller dimensions. When we talk about spatial identity we mean identities connected with the space in common but we deal with the different extensions ranged from local to global.